1998
DOI: 10.1016/s0002-9440(10)65642-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographically Distinct HHV-8 DNA Sequences in Saudi Arabian Iatrogenic Kaposi's Sarcoma Lesions

Abstract: A new member of the gamma-herpesvirus family, HHV-8 (also known as Kaposi's sarcoma (KS)-associated herpesvirus), has been linked to KS and body cavity-based lymphoma. Other members of this family, eg, Epstein-Barr virus, were originally thought to have only one strain, but subsequent analysis revealed different strains correlating to cellular patterns of infectivity and geographical location. To determine whether multiple strains of HHV-8 exist, we compared DNA sequences among KS and body cavity-based lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
(20 reference statements)
1
16
0
1
Order By: Relevance
“…Three of these renal transplant patients, as well as two patients with African endemic Kaposi's sarcoma, had B2 type ORF-K1 genes. Distinct clustering of ORF 26 type B3/C2 polymorphisms were found in the HHV-8 genomes from Saudi Arabian renal transplant patients [Foreman et al, 1998], and they also belonged to the ORF-K1 subtype C [Poole et al, 1999]. In contrast, we identified ORF 26 type B3/C2 patterns in one patient with post-transplant Kaposi's sarcoma and two patients with the African endemic form who had A5 type ORF-K1 genes.…”
Section: Discussionmentioning
confidence: 61%
“…Three of these renal transplant patients, as well as two patients with African endemic Kaposi's sarcoma, had B2 type ORF-K1 genes. Distinct clustering of ORF 26 type B3/C2 polymorphisms were found in the HHV-8 genomes from Saudi Arabian renal transplant patients [Foreman et al, 1998], and they also belonged to the ORF-K1 subtype C [Poole et al, 1999]. In contrast, we identified ORF 26 type B3/C2 patterns in one patient with post-transplant Kaposi's sarcoma and two patients with the African endemic form who had A5 type ORF-K1 genes.…”
Section: Discussionmentioning
confidence: 61%
“…Eight of 10 Saudi males diagnosed with KS had the classic type, which usually affects elderly Mediterranean men or men of eastern European descent. This is explained by the higher rates of human herpesvirus‐8 infection in countries bordering the Mediterranean basin . The two other patients were immune suppressed (AIDS and renal transplant on immune suppression), which are also two independent risk factors for developing KS …”
Section: Discussionmentioning
confidence: 99%
“…Some studies (25,26) have revealed that there are at least three strains of HHV-8 as the result of sequence analysis in various types of KS and suggested the possibility of a geographic distribution of variants. Recently, Nicholoff et al (27) reported geographically distinct HHV-8 DNA sequences in Saudi Arabian iatrogenic Kaposi's sarcoma lesions showing a change of C~T in nucleotide 1086 and a change of G~T in nucleotide 1490. The change of C~T in nucleotide 1086 was also frequently found in our KS samples, but the other nucleotide was not included in our PCR-amplified products.…”
Section: Discussionmentioning
confidence: 99%